Math virtual assistant

Calculators Topics Go Premium About Snapxam
ENGESP

Step-by-step Solution

Solve the equation x^2-3x-4=(x+1)(x-4)

Go
1
2
3
4
5
6
7
8
9
0
x
y
(◻)
◻/◻
2

e
π
ln
log
lim
d/dx
Dx
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Polynomial division | Polynomial and rational functions | Algebra II | Khan Academy

https://www.youtube.com/watch?v=FXgV9ySNusc

Polynomial end behavior | Polynomial and rational functions | Algebra II | Khan Academy

https://www.youtube.com/watch?v=tZKzaF28sOk

Polynomial remainder theorem | Polynomial and rational functions | Algebra II | Khan Academy

https://www.youtube.com/watch?v=MwG6QD352yc

Derivative properties and polynomial derivatives

https://www.youtube.com/watch?v=mzOBlH32qdk

Algebra II: Simplifying Polynomials

https://www.youtube.com/watch?v=WB7gPfsv6rQ
$x^2-3x-4=\left(x+1\right)\left(x-4\right)$

Main topic:

Polynomials

Time to solve it:

~ 0.68 seconds